In a flight of starlings : the wonders of complex systems - Parisi, Giorgio (Penguin Press, 2023)
"From the 2021 Nobel Prize winner in Physics, an enlightening and personal journey into the practice of groundbreaking science. In a Flight of Starlings, already a #1 bestseller in his native Italy, celebrated physicist Giorgio Parisi guides us through his unorthodox yet exhilarating work: investigating the principles of physics by observing the flight of flocks of birds. Studying the movements of these communities, he has realized, proves an illuminating way into understanding complex systems of all kinds--collections of everything from atoms and planets to other animals like ourselves. Along the way, he reflects on the lessons he's taken from a life in pursuit of scientific truth: the importance of serendipity to the discovery of new ideas, the surprising kinship between physics and other disciplines, and the value of science to a thriving society. In so doing, he removes the practice of science from the confines of the laboratory and into the real world. Part elegant scientific treatise, part thrilling journey of discovery, In a Flight of Starlings is an invitation to find wonder in the world around us."--